Summitry in the Americas : a progress report - Feinberg, Richard E. (Institute for International Economics WashingtonUS, 1997)
Explains the timing and historical importance of the Miami Summit. Describes the policy processes - within the US government and among the countries of the hemisphere - that created the Plan of Action endorsed in Miami. Assesses the outcomes of the Miami Summit and offers recommendations for improving and institutionalizing summitry in the Americas.